Perbandingan Aktivitas Ekstrak Kulit Buah Manggis dan Berbagai Antioksidan terhadap Penampilan Broiler - Agung Adi Candra (Politeknik Negeri Lampung., 2015)
The aims of this study to determine the mangosteen peel extract on performance, percentage and carcass performance of broilers. This study used 200 broiler chickens were distributed into five treatments with 10 replications and each group of 4 broiler. The treatment groups were: control / blank, broilers with the addition of anti-oxidants synthesis (vitastress), the chickens are kept by using tocopherol, extracts of mangosteen rind 60 mg, and mangosteen peel extract 120 mg. Broilers were reared in the stable open as tropical enclosure models show weight gain diverse. The highest increase in keoompok mangosteen rind flour administration of 120 mg (equivalent to 2 capsules administration) followed by administration of vitamin E, an antioxidant synthesis and control. Mangosteen fruit extract 120 mg, equivalent to 2 capsules administration can increase body weight gain. While the mangosteen fruit extract 60 (1 capsule) gives the equivalent effect of vitamin E and antioksidang synthesis on the market. This implies the work of the mangosteen fruit extract capable meningkan body weight gain in giving 120 mg (2 capsules per cow per day). While the feed conversion rate (feed Conversion ratio) or defined as the ratio of the ability to convert feed into the ration in the treatment group in order from the smallest is the group with the administration of 2 capsules of 1.04 mangosteen mangosteen deilanjutkan 1 capsule of 1.3; antioxidants and vitamin E sinetesis of 1.4 and 1.7 control. Mangosteen 2 capsules a day is able to provide the ability to convert 1.04 kg of feed into 1 kg of meat. It gives an overview of the advantages for the farmer to use mangosteen peel extract as an antioxidant. Keywords: Mangosteen, Performa, antioxidant, broiler